Functional traits and adaptive capacity of European forests to climate change - Bussotti, Filippo; Pollastrini, Martina; Holland, Vera; Brüggemann, Wolfgang (Environmental and Experimental Botany, 2014)
Increasing temperatures and drought risks through climate change are expected to have several consequences for European forests. Adaptive strategies may include: (i) persistence of the current forest types, thanks to the acclimatization to local conditions and to phenotypic plasticity of the populations; (ii) evolution, or local adaptation, i.e., change in genotype (frequencies) within the same species due to environmental pressure. It is favored by large within population diversity and (when possible) gene flow among populations; (iii) migration and substitution of species; and (iv) extinction of populations with low ecological plasticity, especially at the edges of their distribution or in the case of isolated (relict) populations. Because of the economic and ecological relevance of forests, it is of fundamental importance to apply appropriate forest management to make forests able to cope with the new environmental conditions. This may include changes in the composition and structure of forest stands, selection of adapted provenances of the most important European tree species or, if this is regarded as insufficient, assisted migration (i.e., the use of species suitable for the future climatic conditions) and, alternatively, substitution of native with non native species. The intraspecific (genetic and phenotypic) variability at a given site has been proven to be often higher than the variability among sites. Species with a large distribution range are supposed to have a wide variety of genotypes, allowing them to be adapted to different environmental conditions. Genetic variability and phenotypic plasticity are the key factors for the identification of useful tree genotypes for future forestation programs. Adaptation to drought, i.e., the probably most important future abiotic risk factor for forestry, can be reflected in variation of key functional traits (FT), at morphological, physiological and phenological level. FT utilized to screen for adapted genotypes in common gardens and provenance trials include growth, survival, leaf flushing and senescence, foliar features as leaf mass per area and nitrogen content, water use efficiency (e.g., estimated by analysis of the stable carbon isotopes, d13C) chlorophyll content, photosystem II functioning, and photosynthetic capacity under water shortage. Current modeled simulation of future forest distribution suggests the expansion of forests at the highest latitudes and altitudes, alongside with a reduction in the hottest and driest Mediterranean regions of South Europe. The general expectations, however, may be disproved especially at a regional level, by factors unexpected or not well known, such as possible extreme climatic events and increased roles of parasites/diseases (with negative effects), or high capacity of forest persistence or adaptation (with positive effects). Natural migration and species substitution can be hampered by co-factors of climate change, such as forest fragmentation and increased frequency and intensity of forest fires.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Adaptation; Extinction; functional traits; Local evolution; migration; Phenotypic plasticity; Phenotyping; provenances